2020
DOI: 10.1002/cpt.1789
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Machine Learning in Pharmacovigilance: Estimating Likely Patient Genotype From Phenotypical Manifestations of Fluoropyrimidine Toxicity

Abstract: Dihydropyrimidine dehydrogenase (DPD)‐deficient patients might only become aware of their genotype after exposure to dihydropyrimidines, if testing is performed. Case reports to pharmacovigilance databases might only contain phenotypical manifestations of DPD, without information on the genotype. This poses a difficulty in estimating the cases due to DPD. Auto machine learning models were developed to train patterns of phenotypical manifestations of toxicity, which were then used as a surrogate to estimate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Therefore, ML can be used to identify populations at high risk of developing ADRs, determine the severity of ADRs (Routray et al, 2020), as well as accurately identify patients most susceptible to the toxic effects of specific medicines (Correia Pinheiro L et al, 2020). A clear application of ML to achieve these objectives is AwareDX, a pharmacovigilance algorithm using pharmacogenomic data to predict the sex-specific risk of experiencing ADRs (Chandak and Tatonetti, 2020).…”
Section: Artificial Intelligence In Pharmacovigilancementioning
confidence: 99%
“…Therefore, ML can be used to identify populations at high risk of developing ADRs, determine the severity of ADRs (Routray et al, 2020), as well as accurately identify patients most susceptible to the toxic effects of specific medicines (Correia Pinheiro L et al, 2020). A clear application of ML to achieve these objectives is AwareDX, a pharmacovigilance algorithm using pharmacogenomic data to predict the sex-specific risk of experiencing ADRs (Chandak and Tatonetti, 2020).…”
Section: Artificial Intelligence In Pharmacovigilancementioning
confidence: 99%
“…Artificial intelligence (AI) holds the promise of boosting efficiency of processes and increasing insights into data across all aspects of life, including healthcare, such as for cardiac function assessment or lung cancer screening 1 . In medicines regulation, the use of AI in pharmacovigilance has become a topic of interest, with multiple papers being published in the past few years on potential applications of AI 2–7 …”
Section: Introductionmentioning
confidence: 99%
“…1 In medicines regulation, the use of AI in pharmacovigilance has become a topic of interest, with multiple papers being published in the past few years on potential applications of AI. [2][3][4][5][6][7] A recent industry survey on the use of AI and machine learning in pharmacovigilance indicated that pharmacovigilance organizations intend to move rapidly with the planning, piloting, and production implementation of intelligent automation, while also pointing out that regulatory guidance is a potential challenge. 8 Medicines Regulators also need innovation that can deliver for public health.…”
Section: Introductionmentioning
confidence: 99%